STUDY ON PHENOTYPIC AND GENOTYPIC CHARACTERIZATION OF BACTERIAL SPECIES ISOLATED FROM DECAYED FRUITS - SRINIVASAN G.; USHA RANI M. V. (International Journal of Pharma and Bio Sciences, 2014)
Most of the methods adopted for processing of decayed fruits and degradation of wastes are not economical. In order to achieve 100% resource recovery from wastes, a novel type of waste treatment is to be followed, so that, the recovered byproducts could be used as biofertilizers. The objective of this study is identification of bacteria for studying their phenotypic and genotypic characters using molecular tools and conversion of wastes into biosolids as useful byproducts. Decayed fruit samples were procured and pure culture of bacterial strains were isolated. The isolated strains were subjected for phenotypic analysis of biochemical tests and genotypic gene expressions of 16S rRNA amplification, after which, the bacterial species identified were two strains of Bacillus subtilis, Serratia marcescens, Arthrobacter nicotianae and Corynebacterium singulare. The antibiogram activity was performed in all the cultures. From this analysis, strains were found to be resistant to most of the antibiotics.